An overview of food delivery business / Azyyati Anuar ... [et al.] - Anuar, Azyyati; Mohd Piah, Zainuddin; Mustapa, Siti Noor Syalwani (Faculty of Business & Management, Universiti Teknologi MARA (UiTM) Cawangan Kedah, 2021)
The food delivery business has become a trend or phenomenon not only in Malaysia but also around the world. This food delivery trend is taking place in line with the technological advances of the millennials or generation Y, who are very proficient and live with technological prowess. In particular, Malaysian citizens should learn to accept this as a new norm, especially during the COVID -19 pandemic.